SISTEM PAKAR MENENTUKAN MENU MAKANAN SEHAT UNTUK DIET BAGI PENDERITA DIABETES MELLITUS DENGAN METODE FORWARD CHAINING - Ardiyanto Nugroho (2021)
Food is an important basic human need, but there are differences for people with Diabetes Mellitus where the patient must maintain a good diet, of course with a healthy diet for people with Diabetes Mellitus. The purpose of this study is to facilitate patients suffering from Diabetes Mellitus by implementing the Forward Chaining method so that they can assist in selecting the appropriate food menu. Diabetes Mellitus itself is a chronic metabolic disorder that is caused because the pancreas cannot produce enough insulin in the body or because the body's insulin produced by the body is not used effectively. Diabetes Mellitus data collection was obtained from the National Development University "Veteran" Jakarta, Faculty of Health Sciences, Nutrition Studies Program. This expert system is implemented using the web-based Python programming language which uses calculations from Body Mass Index (BMI), Basal Metabolic Rate (BMR), and Total Energy Expenditure (TEE). The results of this calculation will appear several food recommendations along with menus for breakfast, lunch and dinner.